Charge transfer tuning by chemical substitution and uniaxial pressure in the organic complex tetramethoxypyrene–tetracyanoquinodimethane. Issue 6 (7th January 2015) - Rudloff, Milan; Ackermann, Kai; Huth, Michael; Jeschke, Harald O.; Tomic, Milan; Valentí, Roser; Wolfram, Benedikt; Bröring, Martin; Bolte, Michael; Chercka, Dennis; Baumgarten, Martin; Müllen, Klaus
Abstract : Charge transfer is not enhanced by the larger electron affinity of the acceptor as evident from a comparison of the mixed-stack systems TMP–TCNQ and TMP–F4 TCNQ. Abstract : In the search for novel organic charge transfer salts with variable degrees of charge transfer we have studied the effects of two modifications of the recently synthesized donor–acceptor system [tetramethoxypyrene (TMP)]–[tetracyanoquinodimethane (TCNQ)]. One is of chemical nature by substituting the acceptor TCNQ molecules by F4 TCNQ molecules. The second consists in simulating the application of uniaxial pressure along the stacking axis of the system. In order to test the chemical substitution, we have grown single crystals of the TMP–F4 TCNQ complex and analyzed its electronic structure via electronic transport measurements, ab initio density functional theory (DFT) calculations and UV/VIS/IR absorption spectroscopy. This system shows an almost ideal geometrical overlap of nearly planar molecules stacked alternately (mixed stack) and this arrangement is echoed by a semiconductor-like transport behavior with an increased conductivity along the stacking direction. This is in contrast to TMP–TCNQ which shows a less pronounced anisotropy and a smaller conductivity response. Our band structure calculations confirm the one-dimensional behavior of TMP–F4 TCNQ with pronounced dispersion only along the stacking axis. Infrared measurements illustrating the CN vibration frequency shift in F4 TCNQ suggest however no improvement in the degree of charge transfer in TMP–F4 TCNQ with respect to TMP–TCNQ. In both complexes about 0.1 e is transferred from TMP to the acceptor. Concerning the pressure effect, our DFT calculations on the designed TMP–TCNQ and TMP–F4 TCNQ structures under different pressure conditions show that application of uniaxial pressure along the stacking axis of TMP–TCNQ may be the route to follow in order to obtain a much more pronounced charge transfer.